10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background Venous thromboembolism (VTE) causes preventable harm, and risk-appropriate prophylaxis administration is often suboptimal because of inconsistent practices and gaps in knowledge. The authors disseminated a validated web-based interactive nurse education module on VTE prevention and evaluated nurses' perspectives. Method A descriptive cross-sectional electronic post-education survey of trauma nurses was conducted at nine Level I to II centers in the Consortium of Leaders in the study Of Traumatic Thromboembolism (CLOTT) Network. Data were summarized descriptively and with conventional content analysis. Results Of 922 participants, 817 completed the post-education survey (88.6% response rate). A high proportion of positive ratings were received for applicability (96%), communication (95%), appropriateness (92%), engagement (87%), satisfaction (78%), and preference over other online clinical education modules (77%). Qualitatively, 53.7% responded positively (appropriateness and satisfaction), whereas 40.7% responded negatively (technology and variation in institutional electronic systems). Conclusion Nurses rated the module as applicable to bedside practice. Feedback highlighted role-specific relevance and realistic scenarios and identified cross-site technology and workflow fit as considerations for broader dissemination.